Workshop Kewirausahaan: Bimbingan Teknis Wirausaha Berbasis Media Digital dalam Meningkatkan Mental Techopreneur - Putri Basuki, Fabi Marulita; Nurhajati; Basalamah, Muhammad Ridwan; Nur Rizky, Syahrul (Jurnal SOLMA, 2024)
Background: The use of technology by utilizing various tools such as social media, websites and office automation aims to simplify and reduce working time. Choosing the right digital marketing channel platform is a key step in a digital marketing strategy for digital entrepreneurs. It is important for entrepreneurs to continue to innovate by following effective training and guidance, people can be better prepared to face challenges and carry out their entrepreneurial concepts more successfully. The aim of this research is to provide technical guidance based on digital media in building and improving the technopreneur mentality. Method: The approach proposed in PKM includes the stages of preparation, implementation, reporting and evaluation. Results: By providing a broader view of the development of the Industrial Revolution 4.0, this activity can have a positive impact on the quality, quality and productivity of society, especially in the village of Tuyomerto. Participants' satisfaction with the presentation of material, communication of resource persons, time, and needs for material are positive indicators of the success of the Technical Guidance event. This shows that the event has succeeded in meeting participants' expectations. In addition, having further suggestions from participants is a valuable added value for improving and developing activities in the future. Conclusion: Technology support is a key element in helping participants through certain steps in starting, running and developing a business. Providing very detailed entrepreneurship knowledge and material can help participants in preparing a good action plan for creating a new business unit.